{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

lecture_20

# lecture_20 - MA 36600 LECTURE NOTES WEDNESDAY MARCH 4...

This preview shows pages 1–2. Sign up to view the full content.

MA 36600 LECTURE NOTES: WEDNESDAY, MARCH 4 Variation of Parameters General Method. We explain how to find the general solution of the nonhomogeneous equation a ( t ) y 00 + b ( t ) y 0 + c ( t ) y = f ( t ) . Say that { y 1 , y 2 } is a fundamental set of solutions to the homogeneous equation a ( t ) y 00 + b ( t ) y 0 + c ( t ) y = 0 . Consider the function y ( t ) = u 1 ( t ) y 1 ( t ) + u 2 ( t ) y 2 ( t ) . We have the derivatives y = u 1 y 1 + u 2 y 2 y 0 = ( u 1 y 0 1 + u 2 y 0 2 ) + ( u 0 1 y 1 + u 0 2 y 2 ) y 00 = ( u 1 y 00 1 + u 2 y 00 2 ) + ( u 0 1 y 0 1 + u 0 2 y 0 2 ) + ( u 0 1 y 1 + u 0 2 y 2 ) 0 This gives the expression f ( t ) = a ( t ) y 00 + b ( t ) y 0 + c ( t ) y = u 1 a ( t ) y 00 1 + b ( t ) y 0 1 + c ( t ) y 1 + u 2 a ( t ) y 00 2 + b ( t ) y 0 2 + c ( t ) y 2 + a ( t ) u 0 1 y 1 + u 0 2 y 2 + a ( t ) ( u 0 1 y 1 + u 0 2 y 2 ) 0 + b ( t ) ( u 0 1 y 1 + u 0 2 y 2 ) . Since y 1 and y 2 are solutions of a homogeneous equation, the middle row on the right-hand side is zero. We make the assumptions u 0 1 ( t ) y 1 ( t ) + u 0 2 ( t ) y 2 ( t ) = 0 u 0 1 ( t ) y 0 1 ( t ) + u 0 2 ( t ) y 0 2 ( t ) = f ( t ) a ( t ) We solve for u 1 = u 1 ( t ) and u 2 = u 2 ( t ) by considering a couple of first order differential equations. Multiply the first equation by y 0 2 ( t ) (by - y 0 1 ( t )) and the second by - y 2 ( t ) (by y 1 ( t ), respectively) to find the following systems of equations: y 1 y 0 2 u 0 1 ( t ) + y 2 y 0 2 u 0 2 ( t ) = 0 - y 0 1 y 2 u 0 1 ( t ) + - y 2 y 0 2 u 0 2 ( t ) = - f ( t ) a ( t ) y 2 W u 0 1 ( t ) = - f ( t ) a ( t ) y 2 - y 1 y 0 1 u 0 1 ( t ) + - y 0 1 y 2 u 0 2 ( t ) = 0 y 1 y 0 1 u 0 1 ( t ) + y 1 y 0 2 u 0 2 ( t ) = f ( t ) a ( t ) y 1 W u 0 2 ( t ) = f ( t ) a ( t ) y 1 where we have denoted the function

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}